(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To identify factors associated with palliative care needs among patients with lung cancer receiving chemotherapy at the National Lung Hospital in 2025. Methods: A cross-sectional study was conducted among 160 lung cancer patients undergoing chemotherapy between October 2024 and September 2025. Data were collected through face-to-face interviews using the shortened PNPC questionnaire. Results: Physical support needs were higher among patients with stage III-IV disease (OR = 3.93; p = 0.011) and those hospitalized ≥ 2 times (OR = 2.80; p = 0.011). Psychological and spiritual support needs were greater in female patients (OR = 2.15; p = 0.024) and in those hospitalized ≥ 2 times (OR = 2.62; p = 0.006). Communication needs were higher among patients with monthly income over 10 million VND/month (OR = 9.25; p = 0.035). No significant association was found between medical information needs and patient characteristics (p > 0.05). Conclusion: Palliative care needs were associated with gender, disease stage, and hospitalization frequency. Female patients, those with advanced-stage disease, and those with multiple hospitalizations showed the greatest needs.